Optical Characterization of Sodium Fluorescein In Vitro and Ex Vivo - Xu, Ran; Teich, Wanda; Frenzel, Florian; Hoffmann, Katrin; Radke, Josefine; Rösler, Judith; Faust, Katharina; Blank, Anne; Brandenburg, Susan; Misch, Martin; Vajkoczy, Peter; Onken, Julia Sophie; et al. (Frontiers in Oncology, 2021)
Objective: The utilization of fluorescein-guided biopsies and resection has been recently discussed as a suitable strategy to improve and expedite operative techniques for the resection of central nervous system (CNS) tumors. However, little is known about the optical properties of sodium fluorescein (NaFl) in human tumor tissue and their potential impact on ex vivo analyses involving fluorescence-based methods. Methods: Tumor tissue was obtained from a study cohort of an observational study on the utilization of fluorescein-guided biopsy and resection (n=5). The optical properties of fluorescein-stained tissue were compared to the optical features of the dye in vitro and in control samples consisting of tumor tissue of high-grade glioma patients (n=3) without intravenous (i.v.) application of NaFl. The dye-exposed tumor tissues were used for optical measurements to confirm the detectability of NaFl emission ex vivo. The tissue samples were fixed in 4%PFA, immersed in 30% sucrose, embedded in Tissue-Tek OCT compound, and cut to 10 microm cryosections. Spatially resolved emission spectra from tumor samples were recorded on representative slides with a Confocal Laser Scanning Microscope FV1000 (Olympus GmbH, Hamburg, Germany) upon excitation with lambda exc = 488 nm. Results: Optical measurements of fluorescein in 0.9% sodium chloride (NaCl) under in vitro conditions showed an absorption maximum of lambda max abs = 479 nm as detected with spectrophotometer Specord 200 and an emission peak at lambda max em = 538 nm recorded with the emCCD detection system of a custom-made microscope-based singl¬e particle setup using a 500 nm long-pass filter. Further measurements revealed pH- and concentration-dependent emission spectra of NaFl. Under ex vivo conditions, confocal laser scanning microscopy of fluorescein-positive tumor samples revealed a slight bathochromic shift and a broadening of the emission band. Conclusion: Tumor uptake of NaFl leads of changes in optical properties – a bathochromic shift and broadening of the emission band – possibly explained by the dye’s high pH sensitivity as well as concentration-dependent reabsorption acting. Understanding the ex vivo optical properties of fluorescein is crucial for testing and validating its further applications as an optical probe for intravital microscopy, immunofluorescence localization studies, and flow cytometry analysis.